La formación inicial del profesorado español de Educación Primaria en educación lingüística - José Manuel Vez (Escola Superior de Educação de Paula Frassinetti, 2015)
The insights presented here were gained from my academic involvement, short but intense, while working with my students along the first edition of a pilot course on language education addressed to Spanish student teachers at primary education level. This collection of ideas also includes the contributions made by the students who took part in this university course through their collaborative work in a blog